Resilience Pathways of Motherless Children Post-Divorce: An Exploratory Study - Naura Faradiba Nurul Widad; Soffy Balgies (International Conference on Sustainable Health Promotion, 2025)
Using a qualitative case study design, the research involved two participants: an 18-year-old male and a 22-year-old female who have lived without a maternal role since their parents’ separation. Data were collected through structured interviews and analyzed using thematic analysis to identify resilience dimensions. The findings revealed that despite the absence of maternal support, participants demonstrated adaptive strategies in emotional regulation, impulse control, optimism, empathy, problem analysis, self-efficacy, and positive aspects. The uniqueness of the participants lies in their ability to develop resilience in different yet complementary ways, reflecting how cultural and personal factors shape coping mechanisms. This study emphasizes the importance of social support and internal strengths in fostering resilience, while also highlighting the need for further research with larger and more diverse samples.